Leaf phenology and morphofunctional variation in Myrcia amazonica DC. (Myrtaceae) in gallery forest and campo rupestre'' vegetation in the Chapada Diamantina, Brazil - Silva Moraes, Aline Cristina da; Vitoria, Angela Pierre; Rossatto, Davi Rodrigo [UNESP]; Pedreira de Miranda, Lia d'Afonseca; Funch, Ligia Silveira (Soc Botanica Sao Paulo, 2017)
Myrcia amazonica DC. occurs in gallery forest and campo rupestre'' vegetation in the Chapada Diamantina, Bahia State, Brazil-habitats with contrasting irradiance and humidity conditions. We evaluated variations in aspects of the cost-benefit relationships of leaf maintenance and photosynthetic activity (phenology, leaf age, gas exchange, and photosynthetic pigments) and the maintenance of a positive water balance (leaf water potential, wood density, and leaf attributes) in two populations of M. amazonica occurring in those habitats. Our hypothesis was that this species would show more efficient water use associated with maintaining its leaves for longer periods in campo rupestre'' vegetation rather than in gallery forests-linked to the environmental constraints on campo rupestre'' population (lower water availability and elevated irradiance). We found that individuals growing in campo rupestre'' showed greater stomatal conductance, CO2 assimilation, transpiration rates, leaf thicknesses, leaf succulence, daily water potential amplitudes, and leaf longevity but lower wood densities as compared to the gallery forest population. Even with wide contrasts in terms of all of these parameters, both populations maintained perennial leaf patterns, despite with variations in the intensities and durations of leaf production (being more intense and of shorter duration in the campo rupestre'' population). Myrcia amazonica demonstrated high functional and morphological plasticity of attributes related to its survival and growth in these habitats. Our hypothesis was confirmed, as campo rupestre'' plants showed morphofunctional strategies associated with resource conservation, including more efficient water use.
Keywords: Gas exchange; Phenodynamics; Photosynthetic pigments; Water potential; Wood density